The neuroprotective effects of estrogen on the aging brain. - Norbury, R; Cutter, W; Compton, J; Robertson, D; Craig, M; Whitehead, M; Murphy, D (2003)
The population of the western world is ageing. This increase in the elderly population will inevitably mean a rise in the prevalence of age-related cognitive decline and late-onset neuropsychiatric disorder, such as Alzheimer's disease (AD). There are sex differences in the incidence and age of onset of these disorders. Sex steroids and sex chromosomes are therefore implicated in their pathophysiology. We have identified relevant past and current literature using a Medline search and from the references of relevant papers. These were then reviewed and relevant articles have been summarized and included in the review. Evidence is presented for the wide-ranging actions of estrogen in the brain at the cellular, metabolic and neurotransmitter levels as well as from the cognitive, AD, depression and cerebrovascular perspectives. The authors conclude that it is unlikely that estrogen will become a stand-alone treatment for any of these disorders, although there may still be a role as an adjunctive treatment and as a prophylactic measure.